Energy fluxes and melt rate of a seasonal snow cover in the Moroccan High Atlas. Issue 5 (3rd April 2016) - Boudhar, Abdelghani; Boulet, Gilles; Hanich, Lahoucine; Sicart, Jean Emmanuel; Chehbouni, Abdelghani
ABSTRACT: In this study, we used an energy balance model and two simple methods based on readily available data to identify the processes driving the point-scale energy and mass balance of the snowpack. Data were provided from an experimental site located at 3200 m. All models were evaluated by comparing observed and modelled snow water equivalents. Performances are variable from one season to the next and the energy balance model gives better results (mean of root mean square error, RMSE = 25 mm and r 2  = 0.90) than the two simplified approaches (mean of RMSE = 54 mm and r 2  = 0.70). There are significant amounts of snow sublimation but they are highly variable from season to season, depending on wind conditions (between 7 and 20% of the total). While the main source of energy for melting is net radiation, the amount of heat brought by sensible heat flux is significant for two of the most windy snow seasons. Editor Z.W. KundzewiczAssociate editor not assigned